SCG/Kinjoh mice: a model of ANCA-associated crescentic glomerulonephritis with immune deposits - Neumann, Irmgard; Birck, Rainer; Newman, Mark; Schnülle, Peter; Kriz, Wilhelm; Nemoto, Kyuichi; Yard, Benito A.; Waldherr, Rüdiger; Woude, Fokko J. van der (Kidney international, 2003)
BACKGROUND: Spontaneous crescentic glomerulonephritis-forming/Kinjoh (SCG/Kj) mice spontaneously develop crescentic glomerulonephritis (CGN), systemic vasculitis, and perinuclear ANCA (pANCA), and have been suggested as an animal model for human antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AASV). Since no systematic serologic, immunohistologic, or structural evaluation had been performed thus far, we reinvestigated the development of ANCA and CGN in these mice. METHODS: SCG/Kj mice were subjected to serologic and urinary analysis, as well as histologic evaluation of the kidneys by standard light, immunofluorescence, and electron microscopy at regular intervals during the course of the disease. RESULTS: Perinuclear ANCA developed as early as the 6th week of life, increasing both in frequency and titer in up to 100% of animals at week 20. Crescent formation began at week 10 and peaked at week 16, maximally affecting 57% of glomeruli. Crescent formation was initiated by "activated" podocytes that formed cell bridges between tuft and Bowman's capsule. The typical picture of a diffuse immune complex nephritis was found in all animals as early as 8 weeks. Fluorescence intensity increased with age and became strongly positive for immunoglobulin (Ig)A, IgM, IgG, and C3 in the mesangium and along the peripheral capillary loops. CONCLUSION: Although ANCAs were found in the majority of animals, the massive presence of glomerular immune deposits differed from the pauci-immune pattern found in human AASV, making this model not completely representative for human ANCA-associated CGN. However, the spontaneous and concomitant development of pANCA, small vessel vasculitis, and CGN raises the opportunity to analyze pathogenetic links between these disease manifestations in vivo.
Gesehen am 30.09.2022